2015
DOI: 10.1161/hypertensionaha.114.04945
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Use and Risk of Myocardial Infarction and Stroke in a Hypertensive Cohort

Abstract: Abstract-Recent data suggest that self-reported acetaminophen use is associated with increased risk of cardiovascular events and that acetaminophen causes a modest blood pressure rise. There are no randomized trials or studies using verified prescription data of this relationship. We aimed to assess the relationship between verified acetaminophen prescription data and risk of myocardial infarction or stroke in patients with hypertension. We performed a retrospective data analysis using information contained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…In this issue, Fulton et al 7 used the UK Clinical Practice Research Database (GPRD) to assess the association of acet-aminophen with adverse cardiovascular events. The past decade has seen a surge in the use of computerized healthcare data for pharmacoepidemiologic study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Fulton et al 7 used the UK Clinical Practice Research Database (GPRD) to assess the association of acet-aminophen with adverse cardiovascular events. The past decade has seen a surge in the use of computerized healthcare data for pharmacoepidemiologic study.…”
mentioning
confidence: 99%
“…One of the strengths of the study by Fulton et al 7 is that they supplemented their main analyses with the acetaminophen use propensity estimation and conducted analyses on the matched subsample. The study group used the neighbor nearest propensity matching that is a robust approach to the one-to-one matching.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Nevertheless, a recent study of over 24 000 patients from the UK did not show any association between paracetamol and myocardial infarction or stroke. 12 While observational data such as these may be confounded, they provide some reassurance, and the study should be repeated across international datasets.…”
Section: Are There Side Effects?mentioning
confidence: 99%
“…Evidence suggests a possible association between the use of acetaminophen and elevation in blood pressure, and a cohort study showed an increased risk of acute cardiovascular events in women exposed to acetaminophen . Although these findings might be supported by a mechanism of acetaminophen‐induced inhibition of the cyclooxygenase‐2 enzyme in the vascular endothelium, the overall available evidence on the cerebrovascular and cardiovascular safety of acetaminophen is conflicting . In fact, observational studies have reported relative risks of ACCEs for acetaminophen users, compared with nonusers, ranging from 0.84 (95% confidence interval [CI] 0.74–0.95) to 1.68 (95% CI 1.10‐2.58), suggesting both protective and harmful effects.…”
mentioning
confidence: 99%